Study of degradation in InGaP/InGaAs/Ge multi-junction solar cell characteristics due to irradiation-induced deep level traps using finite element analysis. (15th January 2019) - Kotamraju, Siva; Sukeerthi, M.; Puthanveettil, Suresh E.; Sankaran, M.
Highlights: The detailed optimized structure of InGaP/InGaAs/Ge 3J solar cell is presented. A simulation model showing diffusion length variation is proposed for InGaP & InGaAs. The experimental J-V of 3J solar cell has been compared with the simulated result. Current matching between top and middle cell is presented considering deep level traps. A peak η of 30% has been obtained in the presence of traps and interface recombination. Abstract: We investigated the influence of irradiation-induced deep level traps on the performance of 3J solar cell using two-dimensional numerical simulations. Modeling of solar cell degradation has been performed by systematically considering the trap levels in the top InGaP and middle InGaAs subcells. At the trap concentration of 1 × 10 16 cm −3, simulation results show a conversion efficiency of 26% for AM0 spectrum (1-sun). The results obtained demonstrate that the trap level in p-base InGaAs causes more degradation compared to p-base InGaP region. The combination of 1 × 10 16 cm −3 trap concentration and 1 × 10 4 cm s −1 surface recombination velocity is the point beyond which significant reduction in solar cell output parameters was observed. For the same trap concentration and interface recombination values, 30% conversion efficiency was achieved at concentrated sunlight with current matching among the top and middle cells.